Paclitaxel plus carboplatin versus paclitaxel plus alternating carboplatin and cisplatin for initial treatment of advanced ovarian cancer: Long-term efficacy results: A Hellenic Cooperative Oncology Group (HeCOG) study - Aravantinos, G.; Fountzilas, G.; Kosmidis, P.; Dimopoulos, M.A.; Stathopoulos, G. P.; N. Pavlidis; Bafaloukos, D.; Papadimitriou, C.; Karpathios, S.; Georgoulias, V.; Papakostas, P.; Kalofonos, H.P.; et al. (Annals of Oncology, 2005)
Background: We compared the combination plus Carboplatin plus paclitaxel, which is considered the treatment of choice for initial chemotherapy of advanced ovarian cancer (AOC) with a regimen combining alternating carboplatin and cisplatin plus paclitaxel. The two platinum derivatives have been previously combined as they are not totally cross-resistant and as they share no overlapping toxicities. Patients and methods: Patients with AOC, after the initial cytoreductive surgery were randomized to either 6 courses of paclitaxel at 175 mg/m2 as 3h infusion plus Carboplatin at 7 AUC (Arm A) or Paclitaxel at the same dose plus Carboplatin again at 7 AUC for cycles 1,3,5, while for cycles 2,4,6 Cisplatin at 75 mg/m2 substituted for Carboplatin (Arm B). Results: 247 patients are analyzed. Significant differences were not found, both in terms of PFS (38 vs 39 months, p=0.95) and overall survival (40.6 vs 38.6 months, p=0.79). There was not also difference in 5-year survival rate (35% vs 39%) or 5-year PFS rate (23% vs 28%). Age >60, PS 2, stage IV disease and presence of residual disease were adversely related to the overall survival. Conclusion: Both regimens are well tolerated and effective. Alternating cisplatin with carboplatin does not improve the results compared with the standard combination. © 2005 European Society fr Medical Oncology.
Keywords: Alternating cisplatin with carboplatin; Chemotherapy; Initial treatment; Ovarian cancer